Can Growth Monitoring and Promotion (GMP) improve child growth and development? A critical review of the epidemiological foundations - Leroy, Jef L.; Larson, Leila M.; Brander, Rebecca L.; Frongillo, Edward A.; Ruel, Marie T.; Avula, Rasmi (Elsevier, 2024)
Objectives: GMP programs have been globally implemented for many decades, but the epidemiological foundations of GMP have never been reviewed. We evaluated whether commonly used GMP criteria can be used for diagnosis or screening, i.e., if they accurately identify current or predict subsequent inadequate growth or development in individual children. Methods: We conducted a critical review of the literature and analyzed growth patterns in well-nourished children. We estimated the predictive accuracy of commonly used GMP criteria by regressing growth status and developmental scores at 18 and 24 months on these criteria during infancy, using longitudinal data from high-, middle-, and low-income countries. The root mean square error (RMSE), sensitivity (Se) and specificity (Sp) were used as measures of predictive accuracy. Results: Healthy children follow highly variable growth trajectories which challenges the notion that growth information alone can be used to distinguish between current or subsequent healthy or inadequate growth in individual children. The most used GMP criteria (low weight-for-age Z-score, inadequate weight gain) do not provide a clear diagnosis because they cannot distinguish between being too thin or too short. GMP criteria are also not meaningful for screening individual children because they do not accurately predict (low Se, low Sp, and high RMSE) inadequate growth later in childhood. The same holds for growth indices which do not accurately identify individual children at risk of concurrent or later suboptimal development. Conclusions: GMP, as currently designed, does not have the epidemiological basis needed to justify its widescale implementation. Our results do not challenge the need to support parents of young children, but research is needed to identify how regular meetings with parents can be optimized to improve the nutrition, health, and development of their young children in LMICs.